2018
DOI: 10.1111/nyas.13584
|View full text |Cite
|
Sign up to set email alerts
|

Disease prevention and delayed aging by dietary sulfur amino acid restriction: translational implications

Abstract: Sulfur amino acids (SAAs) play numerous critical roles in metabolism and overall health maintenance. Preclinical studies have demonstrated that SAA-restricted diets have many beneficial effects, including extending life span and preventing the development of a variety of diseases. Dietary sulfur amino acid restriction (SAAR) is characterized by chronic restrictions of methionine and cysteine but not calories and is associated with reductions in body weight, adiposity and oxidative stress, and metabolic changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 126 publications
(171 reference statements)
3
42
0
Order By: Relevance
“…More than 20 years ago, Orentreich and colleagues reported that a reduction in the concentration of a single dietary essential amino acid, methionine (from 0.86% to 0.17% w/w), resulted in a 30% longer lifespan of male Fisher-344 rats [30]. While perhaps more aptly referred to as sulfur amino acid restriction (SAAR) due to the fact that the nonessential sulfur amino acid cysteine is absent in MetR diets, the phenomenon has been replicated in different rodent models [31]. Additional benefits of MetR that overlap with CR despite ad libitum access to food include reductions in bodyweight, fat mass and oxidative stress coupled with improvements in insulin sensitivity as well as changes in circulating insulin, glucose, leptin, adiponectin, IGF-1 and FGF-21 [31,32].…”
Section: Sex Differences In Response To Metr In Preclinical Modelsmentioning
confidence: 99%
“…More than 20 years ago, Orentreich and colleagues reported that a reduction in the concentration of a single dietary essential amino acid, methionine (from 0.86% to 0.17% w/w), resulted in a 30% longer lifespan of male Fisher-344 rats [30]. While perhaps more aptly referred to as sulfur amino acid restriction (SAAR) due to the fact that the nonessential sulfur amino acid cysteine is absent in MetR diets, the phenomenon has been replicated in different rodent models [31]. Additional benefits of MetR that overlap with CR despite ad libitum access to food include reductions in bodyweight, fat mass and oxidative stress coupled with improvements in insulin sensitivity as well as changes in circulating insulin, glucose, leptin, adiponectin, IGF-1 and FGF-21 [31,32].…”
Section: Sex Differences In Response To Metr In Preclinical Modelsmentioning
confidence: 99%
“…Dietary intervention is a common strategy in obesity management; however, whether specific dietary interventions are more efficient than others for weight control is still debated. Dietary restriction of the sulfur amino acids methionine and cysteine has the past decades become increasingly recognized as a research model to promote leanness and longevity in animals [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In a large cross-sectional study of US adults, methionine-rich diets were associated with a higher prevalence of cardiometabolic disease risk factors, i.e. higher levels of cholesterol, glucose, glycated hemoglobin, uric acid and insulin (33). The concentrations of CRP also showed to be higher with higher intake of methionine-rich diet, albeit the trend did not reach statistical signi cance.…”
Section: Discussionmentioning
confidence: 92%
“…Compared to calorie restriction, responses to methionine restriction were found to be more robust over the long-run (27). Dietary methionine restriction has been especially associated with metabolic changes in adipose tissue and liver resulting in enhanced insulin sensitivity and energy expenditure (33). In animal studies, methionine restriction was shown to reduce concentrations of insulin, insulin-like growth factor-1, glucose, and leptin and increased adiponectin (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation